Assessing the feasibility of full robotic interaortocaval nodal dissection for locally advanced gastric cancer. Issue 2 (15th April 2014) - Roviello, Franco; Piagnerelli, Riccardo; Ferrara, Francesco; Caputo, Edda; Scheiterle, Maximilian; Marrelli, Daniele
Abstract Background The clinical value of super‐extended lymph node dissection (D2+) is still debated. This procedure has not been reported using the laparoscopic or robotic approach. Although this technique, in low‐volume centres, could lead to an increased risk of morbidity, in high‐volume centres morbidity and mortality are similar to those of the standard D2 lymphadenectomy. Robotic surgery could overcome the limitations of laparoscopic surgery, especially in the removal of posterior nodal stations. In this report we describe the feasibility of fully robotic interaortocaval lymphadenectomy, following similar steps to those of the traditional open approach. Methods The procedure was a total gastrectomy with oesophago–jejunal Roux‐en‐Y reconstruction in a 73 year‐old male patient with clinically advanced (cT3) gastric adenocarcinoma, located in the lesser curvature (middle‐upper third). The da Vinci® Si HD with a double‐docking robot set‐up was employed. Results The histological specimen examination showed a pT4aN3bM0, Borrmann type III, intestinal histotype, G3 gastric adenocarcinoma. No involvement of resection margins was found (R0 resection). The numbers of total harvested and positive nodes were 57 and 41, respectively; the number of harvested interaortocaval nodes was 14, and all of them were negative for tumour involvement. Operative time for lymphadenectomy was comparable with that of the traditional open approach. The postoperative period was uneventful and hospital stay was 11 days. Conclusions Robotic‐assisted interaortocaval lymphadenectomy is a feasible technique in high‐volume centres for gastric cancer surgery, and should be considered in curative surgery for selected advanced cases, especially for the high‐risk group of lymph node metastases in the posterior area. Copyright © 2014 John Wiley & Sons, Ltd.